(untitled) (ALBACORE Jurnal Penelitian Perikanan Laut, 2025)
Squid jigging fisheries in Indonesia have developed rapidly, leading to a substantial increase in energy consumption due to the growing number of squid jigging units. Traditionally, metal halide (MH) lamps with electrical power ranging from 24 to 30 kW are used as light attractors. This study aimed to design a LED (light-emitting diode) lamp for squid fishing with a light distribution pattern comparable to that of MH lamps and to evaluate its fuel consumption. The research involved the design and construction of an LED-based squid lamp, measurement of light intensity in air, and comparison of fuel consumption between LED and MH lamps under laboratory conditions. Underwater light intensity was measured in the waters of Banten Bay. The electronic system employed components with total LED power of 450 watts. Results showed that the average light intensity of the LED lamp decreased by only 10.57% compared to the MH lamp. The Specific Fuel Consumption (SFC) of MH lamps ranged from 0.00162–0.00176 kg/hp·h, while that of LED lamps ranged from 0.00109–0.00119 kg/hp·h. The LED system achieved a fuel efficiency of 40.54%, indicating a 19.03% improvement compared MH lamps. Further field-scale experiments are required to validate effectiveness in actual squid fishing operations. Key words: intensity, light, measurement, squid